Source attribution, health risk analysis, and policy implications of PAHs and NPAHs in PM $$_{10}$$ in Northern Mexico - Lucy T. González; Ilse María Hernández-Romero; Alberto Mendoza; Aldo I. Ramirez; Yasmany Mancilla; Boris Kharissov; Michael Pérez-Rodríguez; Juan Manuel Alfaro Barbosa; Daniel López Serna; Oxana Kharissova; Andrea Nucamendi; Jesús Abraham Díaz Paéz; et al. (Scientific Reports)
Abstract This research investigates the concentrations, sources, and health risks of polycyclic aromatic hydrocarbons (PAHs) and nitrated PAHs (NPAHs) in particulate matter with an aerodynamic diameter of 10 $$μ$$ m or less (PM $$_{10}$$ ) from critical urban centers in northern Mexico: Metropolitan Monterrey Area (MMA), Chihuahua (CHI), and Ciudad Juárez (CDJ). Advanced gas chromatography-mass spectrometry (GC-MS and GC-NCI-MS) revealed significant PAHs concentrations, with levels in MMA reaching 108.89 ± 99.90 ng/m $$^3$$ , CHI at 100.69 ± 122.60 ng/m $$^3$$ and CDJ at 73.26 ± 90.85 ng/m $$^3$$ . Significantly, 3-nitrofluoranthene (3N-FLA) and 1-nitropyrene (1N-PYR), known for their potent toxicity, were among the most prominent NPAHs, with total concentrations in MMA, CHI, and CDJ at 470.32 pg/m $$^3$$ , 247.26 pg/m $$^3$$ , and 193.20 pg/m $$^3$$ , respectively. Source apportionment using diagnostic ratios (DRs) and principal component analysis (PCA) indicated that biomass burning, vehicular emissions, and industrial activities were the primary sources of MMA. At the same time, CHI and CDJ were influenced more by industrial and diesel emissions. Health risk assessments based on benzo[a]pyrene equivalent (BaPeq) concentrations and excess cancer risk (ECR) demonstrated moderate to significant cancer risks, with CDJ exhibiting the highest NPAHs-related risk. This study makes several significant contributions: it presents the first analysis of PAHs and NPAHs levels in these urban areas, identifies key emission sources, and quantifies associated health risks, providing essential data for developing targeted public health policies and environmental regulations.